Plasma-Polymerized Thiophene-Reduced Graphene Oxide Composite Film Sensor for Ammonia/Amine Detection at Room Temperature - Baliram Nadekar; Yogesh B. Khollam; Shoyebmohamad F. Shaikh; Ajinkya Trimukhe; Rajendra Deshmukh; Pravin S. More; Muhammad Usman Hassan Siddiqui; Abu ul Hassan S. Rana; Marimuthu Palaniswami (Chemosensors, 2023)
Industrialization has led to an increasing need for specific and selective gas sensors in the past few decades. Environmental monitoring of certain volatile compounds such as ammonia is necessary. Advancements in the food storage sector have created the need for cheap and effective amine chemosensors. Classical chemosensors still face several issues, such as a lack of selectivity and low sensitivity toward ammonia and amines. Sensitivity is defined as the relative change in response expressed in percentage. In this work, we have resolved a few issues associated with the ammonia and amine sensors, such as low selectivity, long-term instability, and unreliability under higher temperatures using plasma-polymerized thiophene (PPTh) reduced graphene oxide (rGO) composite films. PPTh films were prepared using RF plasma polymerization with optimized deposition parameters. Several samples were evaluated for their sensing response to understand the optimal PPTh and rGO ratio in the PPTh-rGO composite. These composite PPTh-rGO films have shown 4 times higher sensitivity for ammonia/amines than individual PPTh and rGO films. Ammonia, methylamine (MA), dimethylamine (DMA), and trimethylamine (TMA) were primary analytes and tested for sensing response of the PPTh-rGO composite. The sensitivity measured ranges from 1328 for trimethylamine to 2354 for methylamine at 1000 ppm. The order of sensitivity was found to be MA > Ammonia > DMA > TMA. Polymer swelling, reduced charge carriers, and disruption of conductive pathways can explain possible sensing mechanisms. PPTh-rGO composite films have shown selectivity as high as 110 for ammonia/amine over other commonly used volatile organic compounds. The sensing response of these films is stable for any temperature fluctuations from 30 °C to 150 °C. Additionally, films showed stable sensitivity for over 4 months. Thus, composite films of PPTh-rGO can be effectively used to develop highly selective and stable gas sensors for the environmental monitoring of ammonia/amines.